Serological Assessment of the Early Response to Eradication Therapy Using an Immunodominant Outer Membrane Protein of Helicobacter pylori - Nishizono, Akira (American Society for Microbiology, 1998)
Eradication of Helicobacter pylori infection cures gastritis and prevents recurrence of peptic ulcers. Endoscopy is usually used to evaluate the effectiveness of eradication therapy. We designed a new noninvasive assay system for the early evaluation of eradication of H. pylori infection in which a crude H. pylori outer membrane protein preparation (HPOmp) is used as an antigen, and we determined the sensitivity and specificity of the serological assay system. Immunoblot analysis showed that anti-HPOmp antibodies reacted to a protein with a molecular mass of approximately 29 kDa. In those patients who responded to therapy, the anti-HPOmp immunoglobulin G (IgG) titers measured by enzyme-linked immunosorbent assay (ELISA) at 1 month after the end of therapy were significantly lower than those before treatment (34.8% reduction; P < 0.001), and the posttreatment reduction in the antibody titer was significantly greater than that of the titer measured with a commercially available anti-H. pylori IgG ELISA (34.8% versus 16.1%; P < 0.001). When a 25% reduction of anti-HPOmp IgG titer at 1 month after the end of treatment was taken as the cutoff value for H. pylori eradication, the sensitivity and specificity of our new assay were 75% (51 of 68 treatment responders) and 96% (22 of 23 nonresponders), respectively. Our results indicate that the novel serological test with HPOmp might be a clinically useful tool for assessment of eradication of H. pylori.